Inflammation in Irritable Bowel Syndrome (IBS): Role of Psyllium Fiber Supplementation in Decreasing Inflammation and Physiological Management of IBS - Garg, Pankaj (Turkish Journal of Gastroenterology, 2021)
Cite this article as: Garg P. Inflammation in irritable bowel syndrome (IBS): Role of psyllium fiber supplementation in decreasing inflammation and physiological management of IBS. Turk J Gastroenterol. 2021; 32(1): 108-110.